1992
DOI: 10.1021/bi00122a038
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH on the manganese(2+) activation of and binding to yeast enolase: a functional study

Abstract: The influence of pH on the activation of yeast enolase by Mn2+ was measured by steady-state kinetics. The pH influence on the binding of Mn2+ to apoenolase and the enolase-substrate complex was measured by EPR spectroscopy. At pH values above 6.6, activation by Mn2+ is fit by Michaelis-Menten kinetics, but at higher concentrations of Mn2+, inhibition is observed. Under conditions analogous to the kinetic studies, the enzyme binds two Mn2+ per dimer with a Kd in the micromolar range. In the presence of the subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Activities of other enzymes did not differ greatly in the presence of small amounts (1 to 5 mM) of ammonium sulfate. For ENO, an alternative assay (26) measuring PEP absorbance at 240 nm is a more elegant way to solve the ammonium sulfate problem if measurements in the UV range are possible. In conclusion, ammonium sulfate could have an effect on enzyme activities, and it is better to work with desalted enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Activities of other enzymes did not differ greatly in the presence of small amounts (1 to 5 mM) of ammonium sulfate. For ENO, an alternative assay (26) measuring PEP absorbance at 240 nm is a more elegant way to solve the ammonium sulfate problem if measurements in the UV range are possible. In conclusion, ammonium sulfate could have an effect on enzyme activities, and it is better to work with desalted enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…For most enolases the most effective metal activator is Mg 2+ (Wang & Himoe, 1974; Pietkiewicz & Kustrzeba‐Wójcicka, 1983; Lee & Nowak, 1992a, b). Mg 2+ strongly activates enolase from L .…”
Section: Discussionmentioning
confidence: 99%
“…mesenteroides B‐512FMCM, but Mn 2+ and Zn 2+ are at least equally effective. Mn 2+ strongly activates Candida albicans and Saccharomyces cerevisiae enolases (Lee & Nowak, 1992a, b), but is a weaker activator of the enolase from carp muscle. Zn 2+ induces higher activity than Mn 2+ in carp enolase, but the converse is true for the enolases of yeast and C. albicans (Pietkiewicz & Kustrzeba‐Wójcicka, 1983; Lee & Nowak, 1992a, b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of Cd 2+ and Mn 2~ complexes of yeast enolase using ~I3Cd2*NMR and EPR spectroscopy (Spencer, Brewer & Ellis, 1985;Lee & Nowak, 1992a) indicated that the ligands at the 'catalytic' site are all O atoms and that the 'catalytic' metal ion appears to be more than 12 from the 'conformational' site (Lee & Nowak, 1992b). In contrast, studies of the bis Mn 2* complex of phosphonoacetohydroxamate in the active site of enolase suggested that the two metal ions are bridged by a single O atom of this very strongly bound inhibitor (Poyner & Reed, 1992).…”
Section: Enolasementioning
confidence: 99%